BOOK REVIEW. Issue 2 (27th January 2019) - Regenold, Tracey A.
Abstract: The Culture Code: The Secrets of Highly Successful Groups by Daniel Coyle describes the skills, abilities, and practices of effective professional teams that the author gleaned through interviews and observations. The added, accessible summations of scientific research allowed the author to narrate the discovery of each "secret" as an unanticipated benefit that could be applied in virtually any organization. Coyle's approach to performance and culture creation comes with the welcome intention that readers apply the lessons.